An Economic Analysis of Investment Pattern, Cost of Milk Production and Resource Use Efficiency of Dairy Farms in Mizoram - Sangpuii, Lalrin; Malhotra, R; Priscilla, Laishram (Indian Journal of Dairy Science, 2016)
The study was carried out on 180 milk producing households in Mizoram during the year 2014-15 to analyze the capital investment, cost and returns and the profitability. The farms were classified into small, medium and large categories based on herd size. The average investment per farm was estimated to be ` 146193 for crossbred cow while in case of local cow it was ` 45075/farm. The average productivity of crossbred cow and local cow for the overall farm was 7.45 and 2.24 litres of milk per day. The per litre cost of milk production was highest for small herd size in case of crossbred cow i.e., ` 32.73/day while in case of local cow it was highest for medium herd size i.e., ` 26.58/day. The average net return per litre of milk for crossbred and local cows was ` 15.82 and ` 24.67, respectively. The Cobb-Douglas production function indicated that response to concentrate and veterinary expenses were found to be positive and significant for both the breeds. Lower conception rate through AI, inadequate dry fodder, lack of organized marketing facility, lack of veterinary facility, etc., were the major constraints in milk production.